The N-terminal extension of βB1-crystallin: identification of a critical region which modulates protein interactions with βA3-crystallin - Dolinska, Monika B. (2009)
The human lens proteins β-crystallins are subdivided into acidic (βA1-βA4) and basic (βB1-βB3) subunit groups. These structural proteins exist at extremely high concentrations and associate into oligomers under physiological conditions. Crystallin acidic-basic pairs tend to form strong heteromolecular associations. The long N-terminal extensions of β-crystallins may influence both homo- and heteromolecular interactions. However, identification of the critical regions of the extensions mediating protein associations have not been previously addressed. This was studied by comparing the self association and heteromolecular associations of wild-type recombinant βA3 and βB1 crystallins and their N-terminal truncated counterparts (βA3ΔN30 and βB1ΔN56) using several biophysical techniques including analytical ultracentrifugation and fluorescence spectroscopy. Removal of the N-terminal extension of βA3 had no effect on dimerization or heteromolecular tetramer formation with βB1. In contrast, the self association of βB1ΔN56 increased resulting in homotetramer formation and heteromolecular association with βA3 was blocked. Limited proteolysis of βB1 produced βB1ΔN47, which similar to intact protein formed dimers but in contrast showed enhanced heteromolecular tetramer formation with βA3. The tryptic digestion was of physiological significance, corresponding to protease processing sites observed in-vivo. Molecular modeling of the N-terminal βB1 extension indicates structural features which position a mobile loop in the vicinity of these processing sites. The loop is derived from residues 48-56 which appear critical for mediating protein interactions with βA3-crystallin.